Vote of faith: democracy, desire, and the turbulent lives of priest politicians - Mayblin, Maya (Catholic practice in the Americas, 2025)
"The first work by an anthropologist to explore the unique phenomenon of the mayor-priest, this book offers an essential new angle on emerging debates about secularity as the condition of separation of the religious from the political. Brimming with originality, Vote of Faith is required reading for those interested in the gendered and sexual dimensions of the secular, the plasticity of religion, and the fundamental nature of the world's largest religious institution"--